Improved equipment used by knowledgeable operators does reduce radiation. Issue 6 (May 2017) - Balter, Stephen
Key Points: Improvements in fluoroscopic equipment design and configuration facilitates radiation reduction. Operators should exploit improved equipment and fully apply procedural radiation management techniques. Less radiation did not impair the success rate of treating complex CTO lesions.